Chemotaxis and chemiluminescence responses of synovial fluid polymorphonuclear leucocytes during acute reactive arthritis. Issue 8 (August 1990) - Leirisalo-Repo, M; Lauhio, A; Repo, H
Abstract : The chemotaxis and chemiluminescence responses of polymorphonuclear leucocytes (PMN) of synovial fluid and peripheral blood from patients with acute reactive arthritis were studied. Rates of chemotactic and chemokinetic migration of synovial fluid PMN were significantly decreased. In addition, chemiluminescence responses tended to be depressed, suggesting that the cells were deactivated for both chemotaxis and production of oxygen derived free radicals. Such deactivation has been described previously as a characteristic of synovial fluid PMN in rheumatoid arthritis. Compared with those with a mild disease, patients with severe acute reactive arthritis had higher chemiluminescence responses of synovial fluid PMN to phorbol myristate acetate during acute disease and developed increased migration of peripheral blood PMN towards zymosan treated serum after recovery from the disease. This supports the view that hyperreactive PMN contribute to the development of severe inflammatory symptoms in acute reactive arthritis.